Generating low immunogenic pig pancreatic islet cell clusters for xenotransplantation. Issue 9 (25th March 2020) - Carvalho Oliveira, Marco; Valdivia, Emilio; Verboom, Murielle; Yuzefovych, Yuliia; Sake, Hendrik Johannes; Pogozhykh, Olena; Niemann, Heiner; Schwinzer, Reinhard; Petersen, Björn; Seissler, Jochen; Blasczyk, Rainer; Figueiredo, Constança
Abstract: Xenotransplantation of pancreatic islets offers a promising alternative to overcome the shortage of allogeneic donors. Despite significant advances, either immune rejection or oxygen supply in immune protected encapsulated islets remains major bottlenecks for clinical application. To decrease xenogeneic immune responses, we generated tissue engineered swine leucocyte antigen (SLA)‐silenced islet cell clusters (ICC). Single‐cell suspensions from pancreatic islets were generated by enzymatic digestion of porcine ICCs. Cells were silenced for SLA class I and class II by lentiviral vectors encoding for short hairpin RNAs targeting beta2‐microglobulin or class II transactivator, respectively. SLA‐silenced ICCs‐derived cells were then used to form new ICCs in stirred bioreactors in the presence of collagen VI. SLA class I silencing was designed to reach a level of up to 89% and class II by up to 81% on ICCs‐derived cells. Xenogeneic T cell immune responses, NK cell and antibody‐mediated cellular‐dependent immune responses were significantly decreased in SLA‐silenced cells. In stirred bioreactors, tissue engineered islets showed the typical 3D structure and insulin production. These data show the feasibility to generate low immunogenic porcine ICCs after single‐cell engineering and post‐transduction islet reassembling that might serve as an alternative to allogeneic pancreatic islet cell transplantation.